THE EFFECT OF SEMEN WASHING AND SOYBEAN LECITHIN LEVEL ON MOTILITY AND VIABILITY OF RAM SPERMATOZOA STORED AT 5⁰C - Salmin, S.; Ismaya, I.; Kustopo, K.; Beliarti, E. (Diponegoro University, 2012)
The objectives of this reserarch were to study the effect of semen washing and soybean lecithinlevel on the motility and viability of ram spermatozoa stored at 5⁰C. Semen was collected from threemature rams by artificial vagina. Semen was evaluated by macroscopic and microscopic. Semen wasdivided into ten tubes, the semen of first five tubes was unwashed (W0) and diluted with extender 0%,1%, 2%, 3% and 4% soybean lecithin (L0, L1, L2, L3 and L4). Semen of another five tubes werewashed (W1) then each diluted with similar extender levels. The diluted semen samples were stored at5⁰C and the sperm motility and viability were evaluated each day. The interaction of the semen washingand soybean lecithin levels were no significant differences (P>0.05) but the single factor of soybeanlecithin level was significant differeNces (P<0.05) and the single factor of semen washing were nosignificant differences (P>0.05) on progressive motility and viability of ram sperm.The best extenderwas 3% soybean lecithin (L3) with the percentage of ram sperm progressive motility was 63.18 ± 3.61%and viability was 71.76±2.32%.